Latin American architecture at the Paris Universal Exhibitions of 1867 and 1889 - Maldonado Muñoz, Andrés (2023)
The objective of this article is to study and present the official architectural images of the new Latin American nations through their pavilions. Two exhibitions in Paris have been taken as the scene of political representation, but with a very different character. While the Universal Exhibition of 1867 had a monarchical and imperial vision, the Universal Ex- hibition of 1889 housed a republican spirit, coinciding with the centenary of the French Revolution.